2021
DOI: 10.21203/rs.3.rs-535697/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Superparamagnetic Iron Oxide Nanoparticles Induce Apoptosis in HT-29 Cells by Increasing ROS and Damaging DNA

Abstract: Today, research into nanoparticles for diagnostic and therapeutic use in cancer is on the rise. In the present study, the effect of superparamagnetic iron oxide nanoparticles on the formation of apoptosis in HT-29 cells is investigated.In this study, we investigated the mechanisms of apoptosis induced by superparamagnetic iron oxide nanoparticles after MTT assay and determining the appropriate dose of 2.5 µg / mL to induce apoptosis in HT-29 cells.Superparamagnetic iron oxide nanoparticles increased the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…In the present study, we observed inhibition in cleaved caspase-3 activity in rats treated with DEN, which agree with the results reported by Lin et al (2017) [55]. Fe 3 O 4 nanoparticles induce apoptosis in cancer cells by raising the quantity of reactive oxygen species (ROS) and intracellular calcium, as well as boosting the expression of caspase-3 and caspase-9 and decreasing the expression of Bcl-2, as well as causing direct DNA damage [56]. The expression of cleaved caspase-3 is increased by the Fe 3 O 4 /Cs in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we observed inhibition in cleaved caspase-3 activity in rats treated with DEN, which agree with the results reported by Lin et al (2017) [55]. Fe 3 O 4 nanoparticles induce apoptosis in cancer cells by raising the quantity of reactive oxygen species (ROS) and intracellular calcium, as well as boosting the expression of caspase-3 and caspase-9 and decreasing the expression of Bcl-2, as well as causing direct DNA damage [56]. The expression of cleaved caspase-3 is increased by the Fe 3 O 4 /Cs in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Epigenetic changes related to DNA methylation patterns and the expression of non-coding RNAs are also a potential effect of both iron and iron oxides. According to some authors, IONPs can also induce generation of reactive oxygen species (ROS) and subsequent oxidative damage to DNA and chromatin structure [31][32][33] . In our study, it is well possible that discrete alterations in chromatin distribution detected through the changes in run length matrix and wavelet parameters were the result of early chromatin condensation or changes in euchromatin / heterochromatin ratio.…”
Section: Discussionmentioning
confidence: 99%